2018
DOI: 10.3324/haematol.2018.191841
|View full text |Cite
|
Sign up to set email alerts
|

Gemtuzumab ozogamicin in children with relapsed or refractory acute myeloid leukemia: a report by Berlin-Frankfurt-Münster study group

Abstract: Despite intensified salvage treatments, children with relapsed/refractory acute myeloid leukemia have poor survival. We evaluated Gemtuzumab Ozogamicin (CD33-targeted drug) used on compassionate basis in patients diagnosed from 1995 until 2014 within Acute Myeloid Leukemia-Berlin-Frankfurt-Munster studies and identified 76 patients (<18 years) with highly-advanced and pretreated acute myeloid leukemia [refractory de novo acute myeloid leukemia (n=10), de novo acute myeloid leukemia refractory to relapse (1st e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 30 publications
3
40
1
3
Order By: Relevance
“…However, conclusions cannot easily be drawn, since SCT is mostly performed in children achieving CR2 and in relatively good state [25,26]. However, we suggest, in accordance with previous studies [23,27,28], that allo-SCT in CR2 is resulting in better long-term clinical outcome than chemotherapy only, acknowledging that several studies have reported a few survivors with the latter approach. This difference may be due to the limited 2-year OS-rate reported, and thus, in comparison with 5-and 10-year OS-rates, result in biased outcome in favor of chemotherapy only.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, conclusions cannot easily be drawn, since SCT is mostly performed in children achieving CR2 and in relatively good state [25,26]. However, we suggest, in accordance with previous studies [23,27,28], that allo-SCT in CR2 is resulting in better long-term clinical outcome than chemotherapy only, acknowledging that several studies have reported a few survivors with the latter approach. This difference may be due to the limited 2-year OS-rate reported, and thus, in comparison with 5-and 10-year OS-rates, result in biased outcome in favor of chemotherapy only.…”
Section: Discussionsupporting
confidence: 75%
“…After relapse, the majority of children was treated with an SCT. Outcome seemed better in these patients compared to chemotherapy only, with OS-rates comparable to other recent studies [23,24]. However, conclusions cannot easily be drawn, since SCT is mostly performed in children achieving CR2 and in relatively good state [25,26].…”
Section: Discussionsupporting
confidence: 63%
“…More recent studies have demonstrated that lower doses of GO can produce similar outcomes with less treatment-related mortality, leading to re-approval of GO in adult AML therapy [ 49 , 50 ]. GO was subsequently incorporated into pediatric clinical trials in both relapsed and upfront therapies where it improved EFS and reduced relapse risk; however, OS and CR rates remained unchanged [ 14 , 51 ]. The reduced relapse risk (32.8% vs. 41.3%) when GO was given in upfront therapy in COG AAML0531 was offset by increased treatment-related mortality (8.6% vs. 5.9%) [ 14 ].…”
Section: New Therapymentioning
confidence: 99%
“…При среднем периоде наблюдения 4,3 го да ОВ в общей когорте составила 18 ± 5 %, тогда как у больных, которым проведена ТГСК после гемтузума ба озогамицина, -27 %. Больших различий в ОВ при проведении монотерапии гемтузумабом озогами цином и в комбинации с цитарабином (± винкристин) не обнаружено [83,84].…”
Section: липосомальные формы лекарственных препаратовunclassified
“…В норме обеспечивают клеточный метаболизм. Мутированные формы энзима приводят к накоплению (D) -2ги дроксиглютарата, что нарушает функционирование ряда ферментов и приводит к гиперметилированию ДНК [84]. В целом около 15 % пациентов с ОМЛ име ют мутации либо в IDH1, либо в IDH2 [85,86].…”
Section: препараты эпигенетического действияunclassified